Feed quality and feeding level effects on faecal composition in East African cattle farming systems - Ali, A.I.M.; Wassie, Shimels Eshete; Joergensen, R.G.; Korir, Daniel; Goopy, John P.; Butterbach-Bahl, Klaus; Merbold, Lutz; Dickhoefer, U.; Schlecht, Eva (MDPI, 2021)
Effects of feeding levels below maintenance requirements of metabolizable energy (MER) and of feed supplementation on fecal nutrient and microbial C concentrations were evaluated. In experiment 1, Rhodes grass hay only was offered to Boran steers at 80%, 60%, and 40% of individual MER, while steers at 100% MER additionally received a concentrated mixture. This reduction in MER decreased N, increased fungal C but did not affect bacterial C concentrations in feces. In experiment 2, Holstein × Boran heifers were offered a poor-quality roughage diet without supplement, with sweet potato vine silage or with a urea-molasses block. These two supplements did not affect the fecal chemical composition or fungal C but increased bacterial C concentrations in feces. Across all data, the fungal C/bacterial C ratio was positively related to N and negatively to neutral detergent fiber concentrations in feces, indicating diet-induced shifts in the fecal microbial community.